2001
DOI: 10.1046/j.1469-7580.2001.19860651.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth promoting effects of human placental lactogen during early organogenesis: a link to insulin‐like growth factors

Abstract: Many maternally derived factors may be involved in the regulation of embryonic growth but the control mechanisms involved are poorly understood. Human placental lactogen (hPL) has been implicated in playing a role in the control of embryonic growth. Several investigators suggested that there may be a possible link between the effects of this hormone and insulin-like growth factors (IGFs). In order to determine the growth promoting potential of hPL and involvement of IGFs in the mechanism of action of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…Tenday rat embryos were cultured in serum-depleted medium in the presence and absence of human (h) PL with the addition of Igf antisera. Addition of hPL to the depleted serum significantly improved embryonic growth and development, suggesting that the developing embryo may utilize hPL [21]. In this study, colocalization of mPL-II and Igf2 was observed in trophoblast cells in the labyrinth zone and giant trophoblast cells in the junctional zone of the placenta.…”
Section: Discussionmentioning
confidence: 68%
“…Tenday rat embryos were cultured in serum-depleted medium in the presence and absence of human (h) PL with the addition of Igf antisera. Addition of hPL to the depleted serum significantly improved embryonic growth and development, suggesting that the developing embryo may utilize hPL [21]. In this study, colocalization of mPL-II and Igf2 was observed in trophoblast cells in the labyrinth zone and giant trophoblast cells in the junctional zone of the placenta.…”
Section: Discussionmentioning
confidence: 68%
“…Similar to the growth hormone, hPL contributes to the reduction of insulin sensitivity [44]. hPL has been suggested to play a role in the control of embryonic growth [49]. Finally, lactogen hormones (hPL, hGH, PRL) have been implicated in the regulation of islet mass increase that occurs during normal pregnancy [50].…”
Section: Hormones Associated With Modifications In Insulin Secretion mentioning
confidence: 98%
“…Placental GH [17] and hPL [23] control embryo growth, likely via the opposing actions of insulin and insulin-like growth factors, inducing IR in humans [24]. hPL and prolactin increase maternal food intake by inducing central leptin resistance [17].…”
Section: Healthy Pregnancy: Changes In Glucose Metabolism and Immune mentioning
confidence: 99%